Pengaruh Model Pembelajaran Read, Answer, Discuss, Explain, Create (RADEC) pada Materi Keragaman Budaya Indonesiaku terhadap Keterampilan Berpikir Kritis Siswa Kelas V Sekolah Dasar - Agnes Daralita Situngkir; Jenny Indrastoeti Siti Poerwanti (Universitas Sebelas Maret, 2025)
The purpose of this study was to determine the impact of the Read, Answer, Discuss, Explain, Create (RADEC) learning model on critical thinking skills. This study used a nonequivalent control group design. SDN in Cluster III, Banjarsari District became the population in this study. The sample was obtained through cluster random sampling technique with the results of SDN Sumber 2 as the experimental class and SDN Tirtoyoso as the control class. The research instrument was a descriptive test that measured four indicators of critical thinking skills, namely analysis, problem-solving strategies, clarification, and drawing conclusions. The results showed that the average post-test score of the experimental class increased significantly. These findings indicate that the active and systematic application of the RADEC model can encourage students to think more reflectively, analytically, and creatively in understanding the diversity of Indonesian culture.